2015
DOI: 10.1089/neu.2013.3318
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and Chronicity of Altered Resting-State Functional Connectivity after Traumatic Brain Injury

Abstract: Whereas traumatic brain injury (TBI) results in widespread disruption of neural networks, changes in regional resting-state functional connectivity patterns after insult remain unclear. Specifically, little is known about the chronology of emergent connectivity alterations and whether they persist after a critical recovery window. We used resting-state functional magnetic resonance imaging and seed-voxel correlational analyses in both cross-sectional and longitudinal designs to probe intrinsic connectivity pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 97 publications
9
53
0
Order By: Relevance
“…Many rs-fMRI studies have focused on the default mode, or task negative, network (DMN), a well-characterized network which is active during self-reflective thought but suppressed during attentionally-demanding tasks (4). In adults with TBI, rs-fMRI has revealed altered DMN IC throughout recovery (5-7). Additionally, a recent study of adolescents symptomatic from sports-related concussion identified altered IC within the DMN in even this population (8).…”
Section: Introductionmentioning
confidence: 99%
“…Many rs-fMRI studies have focused on the default mode, or task negative, network (DMN), a well-characterized network which is active during self-reflective thought but suppressed during attentionally-demanding tasks (4). In adults with TBI, rs-fMRI has revealed altered DMN IC throughout recovery (5-7). Additionally, a recent study of adolescents symptomatic from sports-related concussion identified altered IC within the DMN in even this population (8).…”
Section: Introductionmentioning
confidence: 99%
“…The present investigation represents the first longitudinal study to evaluate local neuronal activity restoration in ABI patients. Previous longitudinal fMRI studies in ABI patients have been focused on functional connectivity changes [Falletta Caravasso et al, ; Hillary et al, ; Nakamura et al, ; Venkatesan et al, ]. Nakamura and colleagues showed that functional connectivity strength throughout the whole brain longitudinally decreased in 6 ABI patients, with only one scan from control subjects [Nakamura et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from previous longitudinal fMRI studies in ABI patients have been inconsistent [Falletta Caravasso et al, ; Hillary et al, ; Nakamura et al, ; Venkatesan et al, ], and conclusions have been limited, possibly due to the absence of longitudinal data from matched control subjects [Falletta Caravasso et al, ; Nakamura et al, ; Venkatesan et al, ]. Thus, it is important to systematically investigate the potential roles of brain functional activity in tracking the recovery of consciousness level in ABI patients in a relatively large ABI sample with matched healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic and physiologic brain organization, referred to as the connectome [DeFelipe, ; Sporns et al, ] have been used to distinguish healthy controls from patients with schizophrenia, traumatic brain injury, Alzheimer's disease or depression [Peng et al, ; Prasad et al, ; van den Heuvel et al, ; Venkatesan et al, ]. However, it is not known if brain connectivity patterns present prior to injury can predict post‐injury pathological clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%